Higher Level of Chicken Consumption Associated With Less Severe Venous Disease - Kanokwan Kulprachakarn (2018)
© 2017, © The Author(s) 2017. The aim of this study was to investigate the impact of various food intake in patients with varicose veins. A cross-sectional study was conducted between December 2012 through November 2014. Patients at the outpatient department 101 at Maharaj Nakorn Chiang Mai Hospital, Chiang Mai, Thailand, who were older than > 18 years were invited to participate in this study. The severity of varicose veins was divided into 2 groups according to CEAP (clinical, etiological, anatomical, and pathophysiological) classification: mild type of venous disease (C0-C2) and severe type of venous disease (C3-C6). Patients were interviewed about their demographic data and frequency of meat consumption for varicose veins using Vein Consult Program (VCP). A total of 558 eligible outpatients were recruited for the study. Most patients were female (78.9%) and aged > 50 years (47.1%). Seventeen out of 558 patients were diagnosed with high severity of venous disease (3.0%). Remarkably, significantly higher body weight (73.8 ± 13.9 vs 58.4 ± 11.2 kg, P =.000) and body mass index (28.8 ± 4.4 vs 23.3 ± 3.9 kg/m 2 , P =.000) was found in patients with severe types of venous disease compared with the mild group. Unexpectedly, only chicken intake demonstrated the different association with varicose veins (P =.022). Patients with severe venous disease showed lower frequency of chicken consumption. The results suggested an association of chicken consumption with a reduced chance of developing varicose veins.